Microsatellite DNA fingerprinting of Coffea sp. germplasm conserved in Costa Rica through singleplex and multiplex PCR - Sánchez, Elodia; Solano, William; Gatica-Arias, Andrés; Chavarría, Max; Araya-Valverde, Emanuel (Crop Breeding and Applied Biotechnology, 2020)
A large collection of coffee genetic resources is conserved in Costa Rica. In this study, microsatellite DNA fingerprinting of coffee through singleplex and multiplex PCR approaches coupled with capillary electrophoresis are described. To validate both methods, germplasm of Coffea spp. (Arabica and non-Arabica) and intraspecific F1 hybrids were analyzed using fourteen microsatellite markers. It was observed that through both PCR methods the fingerprinting profile of a subset of samples was identical. The genetic analyses revealed that non-Arabica coffee displayed greater genetic variation than Arabica coffee did. In addition, microsatellite analyses allowed the separation of C. arabica from other species using the principal coordinate analysis (PCoA) approach. The neighbor-joining tree clustering analysis revealed either a grouping of wild genotypes separated from cultivars of C. arabica, or a relation of intraspecific F1 hybrids with parental lines. The utility of our methodology for the characterization of F1 hybrids not previously analyzed through SSR (Simple Sequence Repeats) fingerprinting is demonstrated.